Development and in vitro Evaluation of Bioadhesive Vaginal Tablet using Econazole Nitrate as a Model Drug - Dina W. Ameen (College of Pharmacy University of Baghdad, 2017)
In this study, a bioadhesive dosage form of eoconazole nitrate for vaginal delivery was designed using a combination of bioadhesive polymers: Carbopol 941 p and sodium carboxymethylcellulose or methylcellulose in different ratios. The bioadhesive strength was evaluated by measuring the force required to detach the tablet from sheep vaginal mucosal membrane. It was found that the bioadhesive force was directly proportional to Carbopol 941 p content in the different formulae. The formulae were tested for their swelling behavior using agar gel plate method. The results showed that formulae containing a combination of Carbopol 941 p and sodium carboxymethylcellulose had greater swelling index than those containing a combination of Carbopol 941 p and methylcellulose. In vitro drug release study showed that the release of eoconazole nitrate from Formulae containing  sodium carboxymethylcellulose was faster than its release from those containing methylcellulose.The dissolution profiles of the formula containing Carbopol 941 p alone and those conaining various combinations of Carbopol 941 p and  methylcellulose could be considered similar since their calculated similarity factor values were >50. Formula F3 composed of CP/NaCMC in a ratio 1:1 showed moderate swelling, good bioadhesion and retardation of drug release. Thus, it may be considered a good candidate for vaginal bioadhesive dosage forms. Key words: Bioadhesive, econazole nitrate, vaginal tablet